The impact of Youtube on U.S. politics - Ricke, LaChrystal D. (Lexington Books, 2014)
The Impact of YouTube on U.S. Politics analyzes the broad and evolving political impact of YouTube, specifically addressing political campaigning, communication, and engagement. The text provides a synthesized illustration of the ways in which YouTube has become a requisite tool in U.S. politics.